Tissue-Specific Influence of Lamin A Mutations on Notch Signaling and Osteogenic Phenotype of Primary Human Mesenchymal Cells - Kseniya Perepelina; Polina Klauzen; Anna Kostareva; Anna Malashicheva (Cells, 2019)
Lamin A is involved in many cellular functions due to its ability to bind chromatin and transcription factors and affect their properties. Mutations of LMNA gene encoding lamin A affect the differentiation capacity of stem cells, but the mechanisms of this influence remain largely unclear. We and others have reported recently an interaction of lamin A with Notch pathway, which is among the main developmental regulators of cellular identity. The aim of this study was to explore the influence of LMNA mutations on the proosteogenic response of human cells of mesenchymal origin and to further explore the interaction of LMNA with Notch pathway. Mutations R527C and R471C in LMNA are associated with mandibuloacral dysplasia type A, a highly penetrant disease with a variety of abnormalities involving bone development. We used lentiviral constructs bearing mutations R527C and R471C and explored its influence on proosteogenic phenotype expression and Notch pathway activity in four types of human cells: umbilical vein endothelial cells (HUVEC), cardiac mesenchymal cells (HCMC), aortic smooth muscle cells (HASMC), and aortic valve interstitial cells (HAVIC). The proosteogenic response of the cells was induced by the addition of either LPS or specific effectors of osteogenic differentiation to the culture medium; phenotype was estimated by the expression of osteogenic markers by qPCR; activation of Notch was assessed by expression of Notch-related and Notch-responsive genes by qPCR and by activation of a luciferase CSL-reporter construct. Overall, we observed different reactivity of all four cell lineages to the stimulation with either LPS or osteogenic factors. R527C had a stronger influence on the proosteogenic phenotype. We observed the inhibiting action of LMNA R527C on osteogenic differentiation in HCMC in the presence of activated Notch signaling, while LMNA R527C caused the activation of osteogenic differentiation in HAVIC in the presence of activated Notch signaling. Our results suggest that the effect of a LMNA mutation is strongly dependent not only on a specific mutation itself, but also might be influenced by the intrinsic molecular context of a cell lineage.